Respuesta :

Answer:

x=-12

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

80=4x+4(−4x−16)

80=4x+(4)(−4x)+(4)(−16)(Distribute)

80=4x+−16x+−64

80=(4x+−16x)+(−64)(Combine Like Terms)

80=−12x+−64

80=−12x−64

Step 2: Flip the equation.

−12x−64=80

Step 3: Add 64 to both sides.

−12x−64+64=80+64

−12x=144

Step 4: Divide both sides by -12.

-12x/-12=144/-12

x=-12

Answer:

x = -12

Step-by-step explanation:

-4x - 16  =   -4 • (x + 4)

80 -  (4x +  -16 • (x + 4))  = 0

12x + 144  =   12 • (x + 12)

12 • (x + 12)  = 0

x+12 = 0